Sampled-data control of pan-tilt platform using discrete-time high gain observer - Ullah, Hameed; Malik, Fahad Mumtaz; Saeed, Anjum; Ali Akbar, Zeeshan; Hussain, Sajjad (IOP conference series. Materials Science and Engineering, 2019)
In this paper we have presented the design of sampled-data control algorithm for Pan-tilt platform using Discrete-time High Gain Observer (DHGO). The Pan-Tilt platform is a 2-axis serial robotic manipulator having a nonlinear dynamic model. The design of the control algorithm is carried out in 2 steps. In 1st steps, a continuous time state feedback control law based on feedback linearization is designed which is subsequently discretized. In the second stage, the states of the system are estimated using DHGO. To evaluate the performance of the suggested algorithm extensive simulations are carried out in Matlab Simulink.